Skirting Regulation? Trade Liberalisation, Retailers and the Informalisation of South Africa's Clothing industry. (1st July 2011) - Marlea Clarke,; Shane Godfrey,
Abstract : This article explores the recent history of South Africa's clothing industry, focusing on the rapid decline of formal sector employment and parallel growth in informal work, including small, home-based producers. We show that although the changing global regulatory regime and other external factors have shaped employment patterns in the sector, it is internal factors, particularly the country's powerful domestic retail industry and related changes in domestic sourcing patterns, which are largely responsible for informalisation and the current crisis facing the sector. The article concludes by suggesting that the various 'low-road' strategies adopted by manufactures aimed at competing with imports based on price are unsustainable.